2006
DOI: 10.1108/07363760610674347
|View full text |Cite
|
Sign up to set email alerts
|

The role of value in services: a study in a retail environment

Abstract: PurposeThis paper aims to underline the effects of shopping value on customer satisfaction and to determine its antecedent variables.Design/methodology/approachA qualitative survey through interviews with hypermarket customers was first carried out. It was followed by a quantitative study, carried out in two stages: 199 patrons were first interrogated in order to clarify the outlet characteristics scale. A second set of data was then collected (436 respondents). Factorial analysis, confirmatory factorial analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 31 publications
5
46
0
14
Order By: Relevance
“…Both shopping values (utilitarian and hedonic values) are positively and significant effect on satisfaction that related to Cottet et al (2006). It means that increasing consumers' shopping satis-faction could be manipulated by enhancing consumers' utilitarian and hedonic shopping value (Irani & Hanzaee, 2011), even the variance is low (11.8% in explaining satisfaction).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both shopping values (utilitarian and hedonic values) are positively and significant effect on satisfaction that related to Cottet et al (2006). It means that increasing consumers' shopping satis-faction could be manipulated by enhancing consumers' utilitarian and hedonic shopping value (Irani & Hanzaee, 2011), even the variance is low (11.8% in explaining satisfaction).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the path coefficient showed that relationship's still lower than utilitarian value toward satisfaction, it could be concluded there is emotional reaction in Pasar Dukuh Menanggal that makes them satisfied. It is related to the findings of Cottet et al (2006) that posited positive effect of hedonic value toward satisfaction. Due to this result, the management of the marketplace in Dukuh Menanggal should increase the hedonic value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact o f value on customer satisfaction was studied by [48] defined customer perceived value as "an interactive, preferential and relative experience." Results of their research reveal that both utilitarian and hedonic values are positively related to customer satisfaction.…”
Section: Perceived Valuementioning
confidence: 99%